4x-6+7x+1=-3x-4

Simple and best practice solution for 4x-6+7x+1=-3x-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-6+7x+1=-3x-4 equation:


Simplifying
4x + -6 + 7x + 1 = -3x + -4

Reorder the terms:
-6 + 1 + 4x + 7x = -3x + -4

Combine like terms: -6 + 1 = -5
-5 + 4x + 7x = -3x + -4

Combine like terms: 4x + 7x = 11x
-5 + 11x = -3x + -4

Reorder the terms:
-5 + 11x = -4 + -3x

Solving
-5 + 11x = -4 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
-5 + 11x + 3x = -4 + -3x + 3x

Combine like terms: 11x + 3x = 14x
-5 + 14x = -4 + -3x + 3x

Combine like terms: -3x + 3x = 0
-5 + 14x = -4 + 0
-5 + 14x = -4

Add '5' to each side of the equation.
-5 + 5 + 14x = -4 + 5

Combine like terms: -5 + 5 = 0
0 + 14x = -4 + 5
14x = -4 + 5

Combine like terms: -4 + 5 = 1
14x = 1

Divide each side by '14'.
x = 0.07142857143

Simplifying
x = 0.07142857143

See similar equations:

| 3(3)-2y=-5 | | (3x+11)= | | 4.2x+34.4x=7.0-9.5x | | 8x+8=6-(2x-6) | | -2/3w=60/1 | | (x+89)= | | 5(x-1)-2x=1 | | y=2(-5)-1 | | x-3/8+2/5=4/5x | | 3ln(x+7)=-3 | | 5x^2+x=-9 | | x=w/10y | | 1/6-x=-2x-1/6 | | 8=4/X | | 36π=4/3πr^3 | | 4/9x1/4 | | 4/9*1/4 | | 9z^2+11=12z | | X^7+2X^5+5X^3=0 | | 2/3*2/3= | | (5x^3-4x)/(7x^3-2) | | 5x+-10=-15 | | 1/2x-1/8y=-1/4 | | x+x+0.04+0.40=10.35 | | 3/2x-11/2=-5/2 | | 9-4(3x+7)=2 | | x/4-8=x/5-6 | | 9x-14=32 | | 7/8-1/2= | | 8u^2-2u=o | | 2X-2=(X-5) | | 27=r^3 |

Equations solver categories